Preimpregnation reaction kettle - ZHU JIANBIN; AN GUORUI; WU JIANMING; ZHOU HELI; LIAN HUILIANG (2023)
The utility model discloses a preimpregnation reaction kettle which comprises a kettle body and is characterized in that a stirring device is arranged in the kettle body, one end of a stirring shaft on the stirring device penetrates through a through hole in the center of a flange cover and is connected to the stirring shaft, and the other end of the stirring shaft is connected to a motor through a bearing; the flange cover is further sequentially provided with a feeding port, a liquid inlet, a ventilation port and a temperature detection port. A jacket is arranged outside the kettle body, a steam inlet and a steam outlet are formed in the upper end of the side wall of the jacket, a support is welded to the middle of the side wall, and a presoaking liquid outlet device is arranged on the lower portion of the side wall; the presoaking liquid outlet device is arranged at the bottom of the side wall of the reaction kettle and is matched with production control, so that primary solid-liquid separation can be carr